Urogenital History in Veterans Exposed to High-Dose Sulfur Mustard: A Preliminary Study of Self-Reported Data - Soroush, Mohammad Reza; Ghanei, Mostafa; Assari, Shervin; Khoddami Vishteh, Hamid Reza (Urology Journal, 2009)
Introduction: To date, little information exists regarding urogenital diseases in those who have been exposed to sulfur mustard (SM). We report the self-reported history of urologic conditions and findings on physical examination in a group of male veterans 19 to 26 years after exposed to high-dose sulfur mustard. Materials and Methods: Data on urologic health conditions of a nationwide health survey were used in this study. This survey included all 289 Iranian male veterans who had been exposed to high doses of SM between 1983 and 1989. Demographic data, exposure-related data, health status, and also self-reported lifetime history of urologic conditions were analyzed. History of benign prostatic hyperplasia, recurrent urinary tract infections, pyelonephritis, urinary calculi, kidney failure, and urogenital neoplasms were specifically concerned. Results: The mean age of the veterans was 45.0 ? 7.5 years (range, 30 to 75 years). An interval of 19 to 26 years had passed from exposure to SM. Fifty veterans (17.3%) had a positive history of urinary calculi, 25 (8.7%) had recurrent urinary tract infections, 5 (1.7%) had BPH, and 2 (0.7%) had kidney failure. None of them had experienced urogenital malignancies. Neither recurrent urinary tract infections nor urinary calculi were significantly associated with age, medications and their doses, or SM-induced late complications in other organs. Conclusion: This study adds the prevalence of self-reported urologic conditions to our limited knowledge on SM-exposed veterans’ health condition, without finding any link neither to demographic, nor to the severity of health complications related to the SM exposure.